A Case Study of Incompatible Crossmatch in Referred Cases at The Blood Donor Unit of PMI Kota Surabaya - Showmi, Alin Novia; Ariani, Nia Lukita; Yuliwar, Roni; Roeswanti, Roeswanti (Universitas Tribhuwana Tunggadewi, 2025)
Incompatible crossmatching indicates a serological incompatibility between donor and recipient blood, rendering the donor blood unsuitable for transfusion due to the potential risk of post-transfusion reactions. This study aims to present a case study of incompatible crossmatches in referred cases at the Blood Donor Unit of PMI Surabaya. A descriptive qualitative method with a case study approach was employed to explore two referred cases through detailed narrative analysis. Subject I was a referral case showing incompatibility in the major crossmatch, while Subject II showed incompatibility in the major, minor, and autocontrol tests, and also tested (positive) in the Direct Coombs Test (DCT). Further testing of Subject I at the Blood Donor Unit of PMI Surabaya showed that antibody screening (positive), antibody identification (anti-M), DCT (negative), antigen typing (M antigen: neg), major crossmatch (neg), and auto control (neg). Based on these results, the recommended transfusion for Subject I was crossmatch-compatible blood. For Subject II, the further test results were antibody screening (pos), antibody identification (non-specific antibody), DCT (pos), major crossmatch 1 and 2 (2+), and auto control (4+). The transfusion recommendation for Subject II was to use blood with a major crossmatch agglutination grade lower than that of the auto control. The different cases need different treatments. In future research, information about the history of diagnosis and transfusion history is needed to explore the background of the formation of irregular antibodies.